Survivals of Angiography-Guided Percutaneous Coronary Intervention and Proportion of Intracoronary Imaging at Population Level: The Imaging Paradox - Ng, Andrew Kei-Yan; Ng, Pauline Yeung; Ip, April; Lam, Lap-Tin; Siu, Chung-Wah (Frontiers in Cardiovascular Medicine, 2022)
Background: There is a significant disparity between randomized controlled trials and observation studies with respect to any mortality benefit with intracoronary imaging during percutaneous coronary intervention (PCI). This raises a suspicion that the imaging paradox, which some operators may become over reliant on imaging and less proficient with angiography guided PCI, may exist. Method: This was a retrospective cohort study from 14 hospitals under the Hospital Authority of Hong Kong between January 1, 2010 and December 31, 2017. Participants were patients who underwent first-ever PCI. The association between mortality risks of patients undergoing angiography guided PCI and three tertiles (low, medium, high) of proportion of PCI done under intracoronary imaging guidance at a population level (background imaging rate), were evaluated after confounder adjustment by multivariable logistic regression. Results: In adjusted analysis of 11,816 patients undergoing angiography guided PCI, the risks of all-cause mortality for those was higher in the high tertile group compared with the low tertile group (OR, 1.45, 95% CI, 1.10-1.92, P=0.008), the risks of cardiovascular mortality was higher in the high tertile group compared with the low tertile group (OR, 1.51, 95% CI, 1.08-2.13, P=0.017). The results were consistent with multiple sensitivity analyses. Threshold analysis suggested that the mortality risks of angiography guided PCI was increased when the proportion of imaging guided PCI exceeded approximately 50%. Conclusions: The risks of all-cause mortality and cardiovascular mortality was higher for patients undergoing angiography guided PCI in practices with a higher background imaging rate.